2020
DOI: 10.1172/jci132779
|View full text |Cite
|
Sign up to set email alerts
|

In vivo delivery of synthetic DNA–encoded antibodies induces broad HIV-1–neutralizing activity

Abstract: Pharmaceuticals and, as such, receive salary and benefits, including ownership of stock and stock options. KM receives grants and consulting fees from Inovio Pharmaceuticals related to DNA vaccine development. DBW has received grant funding, participates in industry collaborations, has received speaking honoraria, and has received fees for consulting, including serving on scientific review committees and board series. Remuneration received by DBW includes direct payments, stock, or stock options, and, in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 47 publications
(82 reference statements)
1
47
0
Order By: Relevance
“…The literature describes that pDNA-mAbs can exhibit peak serum concentrations after just 2 weeks and then can express at consistent levels for 2-3 months and decline thereafter as the plasmid is lost from cells and then cleared from the serum due to the natural half-life of immunoglobulin G (IgG) [36][37][38][39][40][41]. Long-term small animal studies show the total duration of pDNA-mAb expression to be at least 1 year [42,43]. However, in contrast to viral vectors, synthetic DNA requires an efficient delivery system.…”
Section: Synthetic Dnamentioning
confidence: 99%
See 3 more Smart Citations
“…The literature describes that pDNA-mAbs can exhibit peak serum concentrations after just 2 weeks and then can express at consistent levels for 2-3 months and decline thereafter as the plasmid is lost from cells and then cleared from the serum due to the natural half-life of immunoglobulin G (IgG) [36][37][38][39][40][41]. Long-term small animal studies show the total duration of pDNA-mAb expression to be at least 1 year [42,43]. However, in contrast to viral vectors, synthetic DNA requires an efficient delivery system.…”
Section: Synthetic Dnamentioning
confidence: 99%
“…A recent study by Schommer et al utilizing chondroitinase ABC to degrade chondroitin, also present in the ECM, describes this enzyme as an alternative to hyaluronidase [99]. More recent studies have addressed the need for hyaluronidase pre-treatment and are utilizing co-formulation with recombinant human hyaluronidase (Hylenex ® ) in non-human primates [43]. The Zika DMAb phase I trial is utilizing this co-formulated approach.…”
Section: In Vivo Synthetic Dna Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Early reports described the use of plasmid vector systems for the generation of antibody like molecules as well as anti-HIV-1 envelope neutralizing F(ab)s [31]. Xu et al reported Synthetic DNA vaccines: prime time is approaching Gary and Weiner 25 [33 ]. This platform continues to advance and DMAbs targeting influenza A and B [34,35], dengue [36], Chikungunya [37 ], Zika [38 ], and Ebola [35,39] with of protection in animal models.…”
Section: Syndna Biologics In the Preclinical Settingmentioning
confidence: 99%